Development and functional characteristics of novel foam concrete. (21st March 2022) - Shang, Xiaoyu; Qu, Na; Li, Jiangshan
Highlights: A novel foam concrete was produced by inorganic bubbles with a core–shell structure. Fire resistance, acoustic characteristics and thermal insulation of concrete were enhanced by the introduction of inorganic bubbles. Robust shell and isolation of inorganic bubbles are the keys to the improvement of functional properties of foam concrete. Industrial wastes and biomass resources were reused into value-added production. Abstract: Sustainable and multi-functional development of lightweight concrete is vital for building construction in the background of global climate change. In this study, a novel inorganic bubble (IB) with a core–shell structure was synthesized by fly ash coating on the surface of the sodium alginate beads. And then the IB was used as fine aggregates to replace the river sand with varied ratios for fabricating the foam concrete with different density levels, the performance of which was evaluated in terms of mechanical properties, thermal conductivity, acoustic characteristics and fire resistance. The results indicated that the introduction of IB could form the cellular structure and achieve the specified density (1200, 1400 and 1600 kg/m 3 ) of the concrete with the alginate dehydration. The 28-day compressive strength and elastic modulus of IB foam concrete increased 53.8% and 81.1% compared with the referenced common foam concrete at the same density level. Double roles of IB (forming agents and fine aggregates) may be the essence for the improvement of mechanical properties. The thermal conductivity of the IB foam concrete reduced 51.8 % compared to the common concrete and is similar to foam concrete. Also, IB foam concrete represents excellent fire resistance in terms of longer fire endurance and multiple partial cracks. Furthermore, the sound absorption was enhanced in the medium frequency (700–1600 Hz) and no obvious promotion was observed in the high and low frequency (50–400 Hz, 1600–3000 Hz). Robust shell and isolation of IB are the keys for the improvement of functional properties of foam concrete.